Evaluating the Impacts of Minigrid Electrification in Sub-Saharan Africa - Sinem H. Ayhan; Giacomo Falchetta; Jan C. Steckel (Institute of Labor Economics (IZA), 2022)
A large share of the population of sub-Saharan Africa (SSA) lacks access to modern energy services. To bridge the electricity access gap, distributed power generation systems such as minigrids and stand-alone photovoltaic systems emerge as attractive options in the power supply solution space. In this study, we analyze the impact of minigrid electrification on household welfare and agricultural development across SSA countries. The empirical analysis makes use of a novel geocoded database covering 1,888 minigrid projects from 27 SSA countries, which is merged with various data sources including satellite-based nighttime light data, vegetation health index, and Demographic and Health Surveys. Our results indicate that minigrid electrification is positively associated with households' electricity uptake, ownership of low-power home appliances, and agricultural employment and productivity, while being effective in changing neither overall labor market outcomes nor the choice of cooking fuels.
Keywords: O13; J43; Q01; Q42; N57; 330; electricity access; minigrids; household welfare; agriculture; sub-Saharan Africa